Les quatrièmes de couverture comme lieu d’inscription d’une représentation de la littérature traduite : romans canadiens d’expression française en traduction polonaise (2000-2016) - Elżbieta Skibińska (Ksiegarnia Akademicka Publishing, 2019)
The Back Cover as a Place for Creating an Image of Translated Literature: Polish Translations of French-Canadian Novels (2000-2016)